UMP entrusted by Japanese company to develop algae production project in Malaysia - Ahmad Hilmy, Agir (Penerbit UMP, 2015)
Universiti Malaysia Pahang (UMP) was tasked by Japanese biofuel research firm IHI NeoG Algae to develop a facility where research projects on algae production could be conducted in Malaysia.